Tuning the selectivity of CO2 hydrogenation using ceramic hollow fiber catalytic modules - Jogdand, Shunottara M.; Bedadur, Prachiti R.; Torris, Arun; Kharul, Ulhas K.; Naidu, V. Satyam; Devi, R. Nandini (Reaction Chemistry & Engineering, 2021)
The unique structural features and advantageous pore distributions of alumina hollow fibers can be exploited to tune the selectivity in heterogeneous catalysis. Formation of a finger-like cavity structure is the unique characteristic of the phase inversion method, which provides a larger surface area to volume ratio desirable for catalytic reactions. This feature, along with a highly porous sandwiched skin layer, makes this architecture superior to conventional powder catalysts or other structured catalyst forms like monoliths. Alumina hollow fibers are prepared by the modified phase inversion method and characterized for their pore size and distribution. Ni metal nanoparticles are uniformly deposited in the Al2O3 hollow fibers to prepare a Ni/Al2O3 catalyst and tested for the CO2 methanation reaction. Suitable reactor and catalyst loading methods are designed and optimized to achieve higher CO2 to methane conversion in a temperature range of 225 to 400 degrees C. The alpha-alumina phase, which is usually reported to be a poor support for Ni in CO2 methanation in the conventional fixed bed configuration, showed high activity when modulated as hollow fibers. Also, the selectivity to CH4 is enhanced and minimal CO formation is observed. The kinetic rate expressions are simulated for the prediction of methane and CO gas evolution at the outlet with temperature. The experimental results for the gas composition are in good agreement with the model predictions. The advantage of such a module reactor is explained based on the mass transfer limitations and consequently the reaction time constants arrived at from the predicted gas compositions.

Tuning of oxygen reduction pathways through structural variation in transition metal-doped Ba2In2O5 - Thundiyil, Shibin; Pandikassala, Ajmal; Kurungot, Sreekumar; Devi, R. Nandini (ChemElectroChem, 2022)
Abstract Oxygen reduction reaction (ORR) can take place either through a two-electron pathway to form H2O2 or through a four-electron pathway to form H2O. Both the reactions are important in the respective fields, viz., H2O2 production as well as fuel cell technology, and rational design of catalysts is mandatory to acquire high energy efficiency in both cases. Here, we report the structure-electrochemical property correlation of a series of perovskite related brownmillerite compounds, Ba2In0.75M0.25O5 (M=Mn/Fe/Co/Ni/Cu), synthesized by solid-state method. On transition metal doping, octahedral distortions were observed, and the highly disordered material tends to follow the 4e transfer mechanism. More symmetrical structures followed the 2e pathway to form H2O2 as the product with high peroxide selectivity. The distortion in the octahedral arrangement can be a descriptor to finetune the selectivity of the catalysts towards the 2e and 4e pathways of ORR.
Keywords: brownmillerite; Descriptors; Electrochemical H2O2 synthesis; Octahedral distortion; oxygen reduction reaction